Pelatihan Teknis Media Streaming Dan Recording Dalam Memaksimalkan Program Kegiatan Ekstrakurikuler Mading Bunaken Di MAN 2 Banyumas - Argiyan Dwi Pritama; Rida Purnama Sari; Muhammad Abdul Kafi Thosien; Hafidz Wibisono; Saeful Hidayat (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
The purpose of this activity is to provide training to students who are members of the Mading Bunaken MAN 2 Banyumas extracurricular activities in technically conducting live streaming in every activity carried out. Implementation of training using lecture methods, discussions, and hands-on practice using Open Broadcaster Software (OBS) studio software as well as training on shooting techniques and equipment settings as well as techniques for using cameras in taking pictures during live streaming. From the results of the activities carried out, it was concluded that 30 trainees were able to use the Open Broadcaster Software (OBS) studio and were able to record images properly while doing live streaming.